2016
DOI: 10.1002/asia.201600157
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Molecular Precursor‐based Synthesis of Ag2Se Nanoparticles and Its Composites with TiO2 for Enhanced Photocatalytic Activity

Abstract: The reactions of different silver(I) reagents AgX (X(-) =iodide, trifluoroacetate, triflate) with selenoethers R2 Se (R=Me, tBu) in a variety of solvents were investigated in relation with their use as precursors for Ag2 Se nanomaterials. Different reaction conditions led to different reactivities and afforded either molecular complexes or metal selenide nanoparticles. The reactions leading to in situ formation of the metal selenide nanoparticles were then extended in the presence of commercial TiO2 (P25) to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 78 publications
2
33
0
Order By: Relevance
“…It should be noted that the CVD‐based synthesis of metal selenide thin films from a seleno‐based precursor has been reported by other groups . In these reports, metal halides were typically treated with selenoethers or organic selenides to form distorted octahedral complexes, which decomposed further under mild to moderate CVD heating conditions or under low‐pressure CVD (LPCVD) to form the metal selenides.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that the CVD‐based synthesis of metal selenide thin films from a seleno‐based precursor has been reported by other groups . In these reports, metal halides were typically treated with selenoethers or organic selenides to form distorted octahedral complexes, which decomposed further under mild to moderate CVD heating conditions or under low‐pressure CVD (LPCVD) to form the metal selenides.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the TWR (350) composite and the dye molecules have affinity to each other such that the larger surface area and the phenyl structure of the rGO sheets enhanced adsorption of dyes and their degradation efficiency. The FTIR results indicated that rGO contains different functional groups, such as hydroxyl, epoxy and carboxylic groups, and the π–π interaction between the aromatic rings of the TPP/WO 3 /EG composite with heterocyclic dye molecules smoothed the generation of hydroxyl radical's for their complete mineralisation . The mechanism of photodegradation of the AB25 can be summarised by the following reactions as presented on scheme …”
Section: Resultsmentioning
confidence: 99%
“…The FTIR results indicated that rGO contains different functional groups, such as hydroxyl, epoxy and carboxylic groups, and the π–π interaction between the aromatic rings of the TPP/WO 3 /EG composite with heterocyclic dye molecules smoothed the generation of hydroxyl radical's for their complete mineralisation . The mechanism of photodegradation of the AB25 can be summarised by the following reactions as presented on scheme trueTPP4pt+4pthv4pt4pt(TPP)*(singlet/tripletexcitation) trueWO34pt+4pthv4pt4ptWO34pt(e-+h+)(photoexcitationofWO3) true(TPP/WO3/RGO)4pt+4pthv4pt4ptWO34pt(h+)+TPPe-(separationofphotoexcitede-/h+pairs) trueTPPe-4pt+4ptnormalO24ptTPP4pt+4ptnormalO2-(radicalformation) trueWO34pt+4ptOH-4pt4ptWO3+4pt…”
Section: Resultsmentioning
confidence: 99%
“…HRMS ESI+ mass spectra were recorded using a Thermo Scientific LTQ-OrbitrapXL instrument equipped with a standard ESI/APCI source. Multinuclear NMR spectra were recorded at room temperature in dry CDCl 3 , on a BRUKER AVANCE 400 instrument operating at 400.13, 100.61, 376.49 and 76.31 MHz for 1 H, 13 C, 19 F and 77 Se, respectively. The 1 H and 13 C chemical shifts are reported in ppm units relative to the residual peak of the solvent (ref.…”
Section: General Experimental Informationmentioning
confidence: 99%